Numerical Simulation of Directional Wave Hydrodynamic Forces: A Study of Surface Roughness - Husnuddin, Aida Sofea Nurina (Universiti Teknologi PETRONAS, 2020)
Developing an offshore structure is not an easy job, because many factors have to be taken into account in order to maintain their lifespan. One way to classify its strength to the strength is to measure the wave intensity shaped against the structure. There are several literature reviews that is taken as reference to ease the process of this research. For this research the parameters that are take account are between two different waves the comparison between short crested wave and long crested wave. The surface roughness analysis with a short-crested wave was not widely applied but are widely used for long crested wave. Because of shortage of data and information, short crested wave touches barely the region yet regarding usage in this industry. The objective of this research is to perform numerical simulation on different cylinders of vertical surface roughness subjected to short waves and assess the impact of the cylindrical surface roughness on the short-crested wave.